Allied health professionals' research capacity: open to interpretation? - Terry Cordrey; Elizabeth King; Owen Gustafson (BMC, 2023)
Abstract Allied health professional research capacity and culture has been the focus of growing research interest of late. The recent study by Comer et al. represents the largest survey of allied health research capacity and culture to date. We congratulate the authors on this work and would like to raise some discussion points in relation to their study. The authors have interpreted their research capacity and culture survey results using cut-off values to indicate a degree of adequacy in relation to perceived research success and/or skill level. To our knowledge, the constructs of the research capacity and culture tool have not been validated to an extent that would enable such an inference to be made. Comer et al. describe perceived individual research success and/or skill as adequate, but the rating of skills in areas necessary for the conduct of original research, such as writing research protocols, ethics submissions, securing funding, and writing for publication range from median scores one to three, which is considered 'less than adequate' on the interpretation scale used by the authors. The survey results for the individual and organisational domains reported in Comer et al. are comparable to other similar studies. However, they uniquely conclude research success and/or skill to be adequate in both domains, which is contrary to the interpretation of the other studies. The interpretation of allied health professional research success and skill offered by Cromer et al. differs from studies with similar results and is contrary to previous reports of insufficient research capacity in terms of research trained and active practitioners within these professions in the UK.